Analisis Penerapan Sistem Pencatatan Akuntansi Terpusat pada Rumah Makan Djogoyudan dalam Mendukung Pengendalian dan Pelaporan Keuangan - Dwi Utami (Jurnal Perpajakan dan Akuntansi (JUPAK ), 2026)
This study aims to analyze the implementation of a centralized accounting recording system at Rumah Makan Djogoyudan and its role in supporting financial control and financial reporting. The study employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation involving individuals responsible for the company's accounting and financial management processes. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which consists of data reduction, data display, and conclusion drawing/verification. The results indicate that Rumah Makan Djogoyudan implements a centralized accounting recording system in which branch offices are responsible only for recording daily transactions and reporting them to the head office. Meanwhile, inventory management, financial control, cost of goods sold calculation, and financial statement preparation are managed by the head office. This system supports financial control by enabling more structured and consistent supervision of branch operations. Furthermore, the centralized accounting recording system contributes to more integrated and controlled financial reporting. However, the use of manual recording procedures at the branch level limits the availability of real-time financial information and may lead to reporting delays. Therefore, the company is encouraged to develop a digital-based accounting recording system to enhance the effectiveness of financial control and financial reporting.